(untitled) (Pulse, 2025)
A 48-year-old male presented with persistent localized pain in the medial aspect of the distal femur (Right)). Diagnosed was established with clinical history examination , Xray, CT and bone scanning along with hematological investigations, as osteoid osteoma. En bloc resection was performed using the mid-vastus approach under spinal anaesthesia. Intraoperative localization of the nidus was achieved through chiseling and macroscopic findings of thickened cortical bone with a small lytic area within thickened bone, and marking the nidus with a K-wire, reconfirmed by C-arm fluoroscopy. An en-block excision of the cortical bone including the nidus was performed with a 7 mm bone biopsy trephine. The bone gap was filled using a cortico-cancellous allograft. Histopathological findings confirmed the diagnosis. The patient had an uneventful postoperative recovery with complete symptom resolution. Pulse Volume 16, Issue 2 2024: 43-46